The community of the (im)political: Being with Otherness (Andamios, Revista de Investigación Social, 2011)
The construction of a political community founded from an identitario locking carries always the confrontation and the extermination of the difference. A community unaware of violence, must be considered as a community made up from its convergence in the bosom of a nothing. In parallel, a community of (im)political, in the way as Giorgio Agamben, Roberto Esposito and Jean-Luc Nancy try to show in their proposals, is the consideration of an empty space that returns propitious for the inscription of the difference and the conviviality with the otherness. To be-in-common, to be-with-other, is to be in the absence, in the impossible unitary identification and in the denial of any closure. To live in the frame of a community of (im)political is to be predisposed to the exposition to the difference, with the becoming of the existence of multiple singularities, with the existence of a heterogeneity in-eradicable where the opening towards the otherness makes possible the celebration of a way of community conviviality.
Keywords: community; politicts; identity; closing; otherness